Silence Fiction : Rethinking (Under) Representations of the “Feminine” Through Social Cognition - Szaloky, Melinda (Cinémas)

(untitled) (Cinémas, 2002)
ABSTRACTThis essay readdresses the issue of the social marginalization of women in light of social cognitive theories of schema- and stereotype-driven perception, reasoning, memory, and behavior. The notions of "fundamental attribution error," "stereotype threat," and "outcome dependency" will help elucidate why women's words and actions have traditionally been construed as less consequential than those of their male peers. Moreover, the essay discusses the benefits of the social cognitive model for film scholarship. It argues that social cognition's comprehensive, micro-level understanding of how our habitual, normative reality is constructed can usefully complement those theories of cinematic defamiliarization that invoke the psychology of the mind (e.g., Deleuze's "time-image").